Evaluation of Market Readiness of Medium and Small-Scale Nonprofit Organizations in Northern India: An Empirical Study - Madan, Pankaj (2009)
The study is a quantitative investigation into the market readiness of medium- and small-scale nonprofit organizations (MSNPOs and SSNPOs), using a measuring instrument suited to the distinct characteristics of nonprofits, to see whether MSNPOs and SSNPOs have strategies to curb competition and whether they are still using conventional marketing or have started using information- and communication-enabled technologies. The survey included 50 MSNPOs and 50 SSNPOs from the spiritual capital of India, selected by stratified random sampling. The responses to a structured questionnaire were recorded using 42 statements of which 33 were measured on a tailor-made scale. The paper provides empirical evidence of the extent to which MSNPOs and SSNPOs differ in their promotion, pricing, and product focus. Statements based on observational surveys of the selected NPOs and interviews with the respondents and customers support the statistical results. The paper ends with a discussion of the implications of the marketing practices of NPOs. The findings from the survey and responses are that neither MSNPOs nor SSNPOs agree in principle about the need for formal marketing for their organizations. Marketing of NPOs remains limited to big and famous NPOs, and the study has proved statistically that North Indian SSNPOs and MSNPOs lack market readiness and need to adopt modern marketing practices used by for-profit organizations or big brand NPOs.